2019
DOI: 10.1021/acs.jpcb.9b05555
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Transport Behavior of CO2 in Ionic Polyimides and Ionic Liquid Composite Membrane Materials

Abstract: Ionic polyimides (i-PI) are a new class of polymer materials that are very promising for CO2 capture membranes, and recent experimental studies have demonstrated their enhanced separation performance with the addition of imidazolium-based ionic liquids (ILs). However, there is very little known about the molecular-level interactions in these systems, which give rise to interesting gas adsorption and diffusion characteristics. In this study, we use a combination of Monte Carlo and molecular dynamics simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Relatedly, for the combined GCMC/MD technique the aim is to use GCMC simulations to predict loading and NPT MD simulations to account for the adsorbate-induced polymer chain dynamics, swelling and plasticization associated with that loading. Approximately a dozen works have used the MC/MD approach to incorporate polymer dynamics and make predictions of adsorption processes with adsorbent polyimides, [44][45][46][47][48] composites with ionic liquids, 49 vinyl polymers, 50,51 PIMs 52,53 and cellulose materials. 54 The workflow of the MC/MD procedure begins with a GCMC simulation on a static equilibrated 'fresh' polymeric framework, which results in the uptake of an initial concentration of adsorbate.…”
Section: Combined Monte Carlo and Molecular Dynamicsmentioning
confidence: 99%
“…Relatedly, for the combined GCMC/MD technique the aim is to use GCMC simulations to predict loading and NPT MD simulations to account for the adsorbate-induced polymer chain dynamics, swelling and plasticization associated with that loading. Approximately a dozen works have used the MC/MD approach to incorporate polymer dynamics and make predictions of adsorption processes with adsorbent polyimides, [44][45][46][47][48] composites with ionic liquids, 49 vinyl polymers, 50,51 PIMs 52,53 and cellulose materials. 54 The workflow of the MC/MD procedure begins with a GCMC simulation on a static equilibrated 'fresh' polymeric framework, which results in the uptake of an initial concentration of adsorbate.…”
Section: Combined Monte Carlo and Molecular Dynamicsmentioning
confidence: 99%
“…Most recent examples include ionic polyimides that incorporate imidazolium-based ILs (Mittenthal et al, 2017 ). Szala-Bilnik et al ( 2019 , 2020 ) studied the impact of the anion in ionic polyimide–IL composite membranes, where the imidazolium functionality is present in both the polymer backbone and the plasticizer. They showed that the ion mobility in pure ILs does not translate to cationic membranes, due to ion coordination with the fixed cation.…”
Section: Developments Toward the Il-based Ftmsmentioning
confidence: 99%
“…), there are several polymer platforms that can leverage the benefits of ILs. These include supported IL membranes (SILMs), , polymerized ionic liquids (PILs), and other hybrid/composite materials such as ionic polyimides. As computer resources have increased dramatically over the last 10–20 years, rational screening approaches for IL design have emerged. Based on a variety of computational approaches (and underlying assumptions), some well-known screening techniques include the Quantum Structure–Property Relationship (QSTR), Volume-Based Thermodynamic (VBT) or Volume-Based Approach (VBA), COnductor-like Screening MOdel for Realistic Solvation (COSMO-RS), , and quantum chemical calculations of single ion pairs, , which have been discussed in a recent review …”
Section: Introductionmentioning
confidence: 99%